Predominant Polarity in Bipolar Affective Disorder: A Scoping Review of Its Relationship with Clinical Variables and Its Implications - Pal, Arghya (Indian J Psychol Med, 2019)
BACKGROUND: Bipolar affective disorder (BPAD) is an episodic psychiatric disorder that is associated with considerable morbidity. Psychiatrists have found it difficult to treat the disorder owing to the variety of presentation and variety of challenges in clinical decision-making. To guide the clinicians, the concept of predominant polarity (PP) in BPAD has become important. This review was conducted to understand the definition, epidemiology, relationship with sociodemographic and clinical parameters, and implications of PP in BPAD. METHODOLOGY: The review was conducted after selecting 17 original research studies from PubMed using appropriate search terms. RESULTS: There is no consensus definition of PP. Epidemiological data showed varied results, although most common PP demonstrated in most studies was depressive polarity. The relation between sociodemographic and clinical parameters also lacked uniformity, although certain patterns could be identified in their relationships. The implications of PP in diagnostics, treatment, and classificatory system are discussed. CONCLUSION: PP in BPAD conveys clinically important information that aids a clinician in decision-making. Further studies are required so that we can understand the neurobiological underpinning of the concept.